2010
DOI: 10.1007/s11668-010-9379-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al(OH)3 Particle Fraction on Mechanical Properties of Particle-Reinforced Composites Using Unsaturated Polyester as Matrix

Abstract: The effect of particle fraction on mechanical properties of particle-reinforced composites was studied using tensile and hardness testing. Unsaturated polyester (UP) was used as polymer matrix, and aluminum hydroxide as the reinforcing particles. The fracture morphology of tensile samples was observed by scanning electron microscopy (SEM). The results showed that the tensile strength and absorbed energy increased to a maximum at 10% particle content and then decreased. With increasing content of aluminum hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…This suggests that the hardness of the composite sample derived is also related to the fillers used. These findings echo those of other researchers, who revealed that the addition of ATH or CC fillers into the UP resin up to 10 to 30 PHR increased the composite hardness value and reduced it when the filler was beyond 30 PHR [21,26]. The hardness values of all these material samples indicate that the fillers and UP resin mixture still provide a homogeneous matrix.…”
Section: Effect Of Fillers On Hardness Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…This suggests that the hardness of the composite sample derived is also related to the fillers used. These findings echo those of other researchers, who revealed that the addition of ATH or CC fillers into the UP resin up to 10 to 30 PHR increased the composite hardness value and reduced it when the filler was beyond 30 PHR [21,26]. The hardness values of all these material samples indicate that the fillers and UP resin mixture still provide a homogeneous matrix.…”
Section: Effect Of Fillers On Hardness Propertiessupporting
confidence: 88%
“…The addition of fillers of 15 PHR and 30 PHR, both ATH and CC, and a mixture of ATH and CC increased the flexural strength and modulus of elasticity of the GFRP composite, in line with the findings of earlier studies. The addition of filler up to 20-25% has been found to increase flexural strength, and a value greater than 25% begins to cause a decrease [21,22,25]. The higher the number of fillers, the higher the tendency of the filler to agglomerate.…”
Section: Effect Of Fillers On Flexural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…High ATH loads also result in an increase in the modulus of elasticity and a decrease in fracture elongation, increasing the stiffness and brittleness of the composite. The modulus of elasticity of the UP resin’s 40% ATH load is 2.41 Gpa, 29.57% higher than the modulus of elasticity of the pure UP resin [ 35 ]. Increasing the ATH load of a GFRP composite tends to reduce the bending strength.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic modulus indicates the stiffness of the material. With increase in amount of Al (OH) 3 , the particle/matrix surface area increases and the aggregates are formed which results in higher modulus [2]. Fig.…”
Section: A Compression Testmentioning
confidence: 97%